Patrón reproductivo en Dendrobates pumilio (Anura: Dendrobatidae) - Prohl, Heike (1997)
The reproductiye activity of the diurnal poison frog Dendrobates pumilio was studied from July to December 1993 in a tropical lowland raínforest of Costa Rica: Hitoy Cerere. The author yisited the study area for 143 days. The study area of 748 m2 was divided into squares of 4 m in order to report the spacial distribution of the frogs. AH adult frogs were toec1ipped for identification. Each hour of observation all males were located and activity (calling and mating) was recorded. Temperature was controlled every hour ofobservation and precipitation was measured daily. Furthermore, during 4 days the author followed one male and recorded the temporal distribution of its behaviors: 1. calling, 2. displacement (movement), 3. feeding, 4. mating, 5. parental careo A total of 20 males and 29 females was found, of which 14 males defended a territory for more than 10 days. Calling activity (calling territorial males in proportion to all territorial males) was highest in the moming with a peak activity between 8.00 and 10.00 hours and mating activity washighest between 9.00 and 10.00 hours. At 7.00 and 8.00 hours the calling activity showed a slight correlation with the temperature. Optimal temperature for calling was between 23.5°C and 25.0°C. Precipitation had a positive influence on calling and mating activity. Dendrobates pumilio showed continous reproduction during the investigation period, however, mating activity was highest in September and October, with a daily average of 0.58 and 0.56 matings. Activity declined considerably towards the end of the year. The observations of one males' behaviour matched the general activity pattems. Feeding took place during and after calling and territory control, but was not consistent with mating. Displacement was re\ated to calling, mating and feeding activity. As in sorne other dendrobatids, D. pumilio's reproductive activity is uncyclical and dependent on raínfall. Mating activity reached its peak before months of highest precipitation (November, December), which could be an adaptation to provide water contaíning plant axils for tadpole development. Physiological constraints should prevent activity during hol and dry periods in most frogs. Apparently, the optimal temperature range for reproductive activity in D. pumilio is around 24°C and narrow. Consequently, if global climatic changes cause increasing temperatures and alter precipitations, shifts in activity patterns and geografical distribution could be expected.